2020
DOI: 10.3168/jds.2019-16818
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intramammary infection in early lactation with non-aureus staphylococci in general and Staphylococcus chromogenes specifically on quarter milk somatic cell count and quarter milk yield

Abstract: This longitudinal study aimed to evaluate the impact of subclinical intramammary infection (IMI) with nonaureus staphylococcal (NAS) species in the first 18 d in milk (DIM) on the quarter milk somatic cell count (qSCC) and quarter milk yield (qMY) during the first 4 mo of lactation in Holstein Friesian heifers. Quarter milk samples were collected from 82 heifers from 1 to 4 DIM until 130 DIM on a biweekly (14 d) basis for determination of the qSCC; qMY data were available through the automatic milking systems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 45 publications
(86 reference statements)
6
23
0
Order By: Relevance
“…Part of the discrepancies among different studies can be attributed partly to the great variation in study design, such as length of the follow-up period, number of herds and animals, definition of IMI, and selection of included animals (e.g., heifers vs. multiparous cows, animals at the start of lactation vs. any lactation stage) but also the identification methods (i.e., phenotypic vs. genotypic methods). In our previous work, we documented that NAS IMI between 1 and 4 DIM and in the first 18 DIM resulted in a higher qSCC during the first 4 mo of lactation, but had no effect on qMY (Valckenier et al, 2019(Valckenier et al, , 2020. However, we observed a difference between S. chromogenes and other NAS species in terms of occurrence, persistence, and effect of IMI in the first 18 d after calving on later qSCC and qMY.…”
Section: Discussionmentioning
confidence: 43%
See 3 more Smart Citations
“…Part of the discrepancies among different studies can be attributed partly to the great variation in study design, such as length of the follow-up period, number of herds and animals, definition of IMI, and selection of included animals (e.g., heifers vs. multiparous cows, animals at the start of lactation vs. any lactation stage) but also the identification methods (i.e., phenotypic vs. genotypic methods). In our previous work, we documented that NAS IMI between 1 and 4 DIM and in the first 18 DIM resulted in a higher qSCC during the first 4 mo of lactation, but had no effect on qMY (Valckenier et al, 2019(Valckenier et al, , 2020. However, we observed a difference between S. chromogenes and other NAS species in terms of occurrence, persistence, and effect of IMI in the first 18 d after calving on later qSCC and qMY.…”
Section: Discussionmentioning
confidence: 43%
“…Some studies found no significant differences in quarter milk SCC (qSCC) between different NAS species (Hogan et al, 1987;Bexiga et al, 2014), whereas others noted that important species differences exist (SuprĂ© et al, 2011;Fry et al, 2014). Moreover, in our previous study, we concluded that IMI with S. chromogenes starting in the first 18 DIM resulted in a significantly higher qSCC during the first 130 DIM, whereas IMI with the group of other NAS species had no effect on qSCC (Valckenier et al, 2020). Some NAS species, such as Staphylococcus chromogenes, S. simulans, and S. xylosus, are called species "more relevant for udder health" as they are able to increase the qSCC to a level comparable to that of S. aureus (SuprĂ© et al, 2011), as substantiated by Fry et al (2014).…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…together and treated them as a single group. While there is an increasing body of evidence to suggest that all NAS are not equal (Valckenier et al, 2020;Wuytack et al, 2020), we took this approach to facilitate comparison with earlier research in the area. A more detailed analysis of the outcomes and potential roles of the individual NAS spp.…”
Section: Discussionmentioning
confidence: 99%